2013
DOI: 10.1007/s10802-013-9730-3
|View full text |Cite
|
Sign up to set email alerts
|

Personality Dimensions as Common and Broadband-Specific Features for Internalizing and Externalizing Disorders

Abstract: Several researchers have suggested that the nature of the covariation between internalizing and externalizing disorders may be understood better by examining the associations between temperament or personality and these disorders. The present study examined neuroticism as a potential common feature underlying both internalizing and externalizing disorders and novelty seeking as a potential broad-band specific feature influencing externalizing disorders alone. Participants were 12- to 18-year-old twin pairs (63… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 62 publications
3
54
0
1
Order By: Relevance
“…Rather, the common factor is likely to reflect some systematic variability in behavior. Recently, conceptual work has argued (Clark 2005), and empirical work (Hink et al 2013; Kotov et al 2010) has found, that neuroticism has strong and consistent associations with all common mental disorders, suggesting that the common factor could reflect neuroticism. In preschool-aged children, this common factor may manifest as negative emotionality (NE), which may be less influenced by cognitive factors implicated in neuroticism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, the common factor is likely to reflect some systematic variability in behavior. Recently, conceptual work has argued (Clark 2005), and empirical work (Hink et al 2013; Kotov et al 2010) has found, that neuroticism has strong and consistent associations with all common mental disorders, suggesting that the common factor could reflect neuroticism. In preschool-aged children, this common factor may manifest as negative emotionality (NE), which may be less influenced by cognitive factors implicated in neuroticism.…”
Section: Discussionmentioning
confidence: 99%
“…This additional step enhances our understanding of the latent structure of psychopathology by describing the nature of the underlying pathological processes. Temperament has garnered much support as a basis for understanding the structure of psychopathology, as different temperament dimensions have been consistently linked to the internalizing and externalizing spectra (e.g., Clark 2005; Hink et al 2013). However, these associations have rarely been examined in studies of the latent structure of youth psychopathology and, when they have been examined, have often relied on the same informant for both psychopathology and temperament.…”
mentioning
confidence: 99%
“…High negative emotionality also interferes with positive social relationships and socialization of behavior (Waldman et al, 2011). Many researchers have found a positive association between negative emotionality and conduct problems (e.g., Gjone & Stevenson, 1997; Hink et al, 2013), although others have not (e.g., Furnham & Thompson, 1991; John, Caspi, Robins, Moffitt, & Stouthamer-Loeber, 1994). …”
Section: The Developmental Propensity Modelmentioning
confidence: 99%
“…For example, the personality trait of neuroticism has been shown not only to account for comorbidity between anxiety and depressive disorders (Middeldorp, Cath, Van Dyck, & Boomsma, 2005) but, more generally, to underlie comorbidity of these disorders with PD (e.g., Hink et al, 2013; JylhĂ€, Melartin, & IsometsĂ€, 2009). In contrast to approaches that rely on categorical diagnoses, a dimensional classification system would allow the complexity of personality pathology that is evidenced by high comorbidity rates to be captured fully and represented with greater clarity and specificity, thus furthering our understanding of a wide range of psychopathology.…”
Section: Problems With the Current Categorical Pd Diagnostic Systemmentioning
confidence: 99%